If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -7 = 5(x + 1) Reorder the terms: -7 + 10x = 5(x + 1) Reorder the terms: -7 + 10x = 5(1 + x) -7 + 10x = (1 * 5 + x * 5) -7 + 10x = (5 + 5x) Solving -7 + 10x = 5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 10x + -5x = 5 + 5x + -5x Combine like terms: 10x + -5x = 5x -7 + 5x = 5 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + 5x = 5 + 0 -7 + 5x = 5 Add '7' to each side of the equation. -7 + 7 + 5x = 5 + 7 Combine like terms: -7 + 7 = 0 0 + 5x = 5 + 7 5x = 5 + 7 Combine like terms: 5 + 7 = 12 5x = 12 Divide each side by '5'. x = 2.4 Simplifying x = 2.4
| 4x-29.2=7.5x-6.8 | | 3g-21=20+2g | | 5n=20(4+0.25) | | (X+2)(x^2-1)=0 | | 7685=345-5d | | -51z=-11.73 | | 2243+5754+789= | | 14*(3/2+x)=28 | | x^2+2r-360=0 | | 6x^2-22x-20=0 | | 14(3/2+x)=28 | | 6-0.25f=3 | | 6.4x=0.2816 | | -6t+17=3t-34 | | -23z+234=970 | | 0.4y-8=9-0.6y | | .01x+.10x+.25(31-2x)=3.46 | | 108+4u=2u | | -.8x+2.2=7 | | 5x+21-2x=27 | | -3.7-5x-8.3-2x=-6x+11.4 | | 6.4x=0.2016 | | 4a^2-10=54 | | (72.34)2.1= | | -3(3x+15)-(10-1x)=35 | | 28x-7=26x+7 | | 11x-9+3x-4=10x-2+3x | | 7n^2+10=-75 | | -3(3x+15)-(10-x)=35 | | 3[w-12]+30= | | 6.32-4.7= | | 45-[4-2x-4(y+7)]=-4(1+3y)-[4-3(y+2)-2(2y-5)] |